A Novel Wild-Type Lacticaseibacillus paracasei Strain Suitable for the Production of Functional Yoghurt and Ayran Products - Ioanna Prapa; Chrysoula Pavlatou; Vasiliki Kompoura; Anastasios Nikolaou; Electra Stylianopoulou; George Skavdis; Maria E. Grigoriou; Yiannis Kourkoutas (Fermentation)
Raw goat and ewe’s milk samples were used for the isolation of seven lactic acid bacteria new strains. After testing hemolytic activity and resistance to antibiotics, specific functional properties were evaluated; Lactococcus lactis subsp. lactis FBM_1321 and Lacticaseibacillus paracasei FBM_1327 strains resulted in the highest cholesterol assimilation percentages ranging from 28.78 to 30.56%. In addition, strong adhesion capacity to differentiated Caco-2 cells (1.77–21.04%) was mapped, and the lactobacilli strains exhibited strong antagonistic activity against foodborne pathogens compared to lactococci. The strains were able to grow at low pH and high NaCl concentrations, conditions that prevail in food systems (cell counts ranged from 1.77 to 8.48 log CFU/mL after exposure to pH 3 and from 5.66 to 9.52 log CFU/mL after exposure to NaCl concentrations up to 8%). As a next step, freeze-dried immobilized Lc. paracasei FBM_1327 cells on oat flakes were used for the preparation of functional yoghurt and ayran products. Cell loads of the functional strain remained high and stable in both products (7.69 log CFU/g in yoghurt and 8.56 log CFU/g in ayran after 30 days of storage at 4 °C) throughout their shelf life. No significant changes in the volatile profile were noticed, and the new products were accepted by the panel during the sensory evaluation.